Temporal and spatial resolved SuperDARN line of sight velocity measurements corrected for plasma index of refraction using Bayesian inference. Issue 4 (24th April 2015) - Spaleta, J.; Bristow, W. A.; Klein, J.
Abstract Recent work by Gillies et al. (2012, 2009, 2010) has sought an explanation for the SuperDARN line‐of‐sight velocity underestimate of ionospheric plasma velocity. The reason for the underestimation is thought to be from the modification of the measured Doppler shift of the backscattered signal due to phase refractive index of the ionospheric plasma in the scattering region. Presented here is an analysis technique to estimate the plasma drift velocity, correcting for the index of the refraction of the scattering medium. The technique requires dual frequency SuperDARN observations and calculates velocity from the phase of the SuperDARN autocorrelation function (ACF). Both plasma velocity and plasma density are treated as independent unknowns, and self‐consistent error estimates are generated for each. This new technique was employed at the McMurdo radar, resulting in estimates of plasma velocity on scales relevant to existing SuperDARN data products. The McMurdo dual frequency analysis also provides a new SuperDARN data product, an estimate for the plasma density in the ionospheric region derived wholly from SuperDARN backscatter.